1998
DOI: 10.1103/physrevlett.80.1094
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Quenching of Optical Transitions in Capped Self-Assembled Quantum Dot Structures

Abstract: Strain-induced quenching of optical transitions has been found in capped self-assembled quantum dot structures. Light absorption at the E 1 and E 1 1 D 1 critical points of InSb islands buried in InP disappears for nominal InSb thicknesses lower than 10 monolayers as a consequence of the strain produced inside the islands by the cap layer. Certainly, this strain increases as the InSb deposition diminishes, changing the band lineup of the system from type-I to type-II and therefore drastically reducing the osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Recently, Prieto et al 5 predicted this offset to be as small as 0.05 eV and they showed that if uncapped InSb dots are grown on an InP substrate the band alignment is type I, and the dots have a direct band gap. However, if these dots are capped with another InP layer, the InP capping layer compresses the InSb dots.…”
Section: Indirect Gap Dots: Insb/inpmentioning
confidence: 98%
“…Recently, Prieto et al 5 predicted this offset to be as small as 0.05 eV and they showed that if uncapped InSb dots are grown on an InP substrate the band alignment is type I, and the dots have a direct band gap. However, if these dots are capped with another InP layer, the InP capping layer compresses the InSb dots.…”
Section: Indirect Gap Dots: Insb/inpmentioning
confidence: 98%
“…Self-organized QD's have been studied in semiconductor systems such as Ge/Si, 1 InAs/GaAs, 2,3 In x Ga 1Ϫx As/GaAs, 4 and InSb/InP. 5 Many questions regarding their vibrational modes, excited electronic states, and electron-phonon interactions remain unanswered. In case of self-organized Ge QD's grown by molecular beam epitaxy ͑MBE͒ on Si substrates in the Stranski-Krastanov growth mode, quantum-confined emission has recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The optical properties of such islands have been mainly studied by incoherent methods. [4][5][6][7] Driven by the search for blue-green-emitting semiconductor materials, the fabrication [8][9][10][11][12][13] and optical characterization [14][15][16][17][18] of self-assembled II-VI islands have recently been the subject of intensive research. Only little is known about the coherent properties of these structures, giving information about exciton scattering and biexciton formation.…”
mentioning
confidence: 99%